Kualitas Umbi Empat Varietas Bawang Merah dari Berbagai Perlakuan Pematahan Dormansi - Azmi, Chotimatul; Ningtyas, Wilujeng Cahya; Hermanto, Catur; Aswani, Nazly; Rahayu, Astiti; Manik, Fatiani; Merdeka, Agnofi F. (Agropross : National Conference Proceedings of Agriculture, 2022)
Cucumber is an annual plant whose life is creeping or climbing on twisted or spiral handles with a fairly Information regarding the quality of shallot bulbs is still limited. Therefore, an experiment was conducted to determine the quality of shallot bulbs from the results of the shallot dormancy breaking treatments. The research was conducted at the Indonesian Vegetable Research Institute from February to April 2018. The tubers of ten breaking dormancy treatments of four shallot varieties were tested for quality including water content, vitamin C, texture and sulfite content and total soluble solid (TSS) with two replication. The results showed that the variety had an effect on the total soluble solid (TSS), sulfite content, texture and vitamin C content. The treatment of dormancy breaking had an effect on the content of soluble solids (TSS), texture and vitamin C. The water content was not affected by the variety and the treatment of dormancy breaking of the shallot bulbs.